Impact of financial literacy on savings among university students in Uganda: a case study of makerere university business school - Phillipa Happy Katali (Uganda Christian University, 2026)
This study sought to investigate the effect of financial literacy on savings among university students. Makerere University Business School (MUBS) formed the case study. It is important to note that the study was informed by the following three objectives: assessing the effect of financial knowledge on saving among university students, analyzing the effect of financial awareness on saving among university students, and exploring the effect of financial skills on the creation of a saving culture among university students. This study employed a cross-sectional survey design with a quantitative research approach. It targeted 370 university students pursuing the Bachelor of Commerce course at the third year. A simple random sampling design was employed to select 192 participants. The results indicated that the level of financial literacy among MUBS students is very high, with mean scores of 3.86 for financial knowledge, 3.79 for financial awareness, and 3.91 for financial skills. Moreover, financial skills were found to be the strongest among the three, with the highest mean score recorded for budgeting skills (4.22), where 87.6% of the students confirmed their ability to create and follow budgets. However, gaps in financial literacy were also identified. Compound interest understanding recorded the lowest mean among the financial knowledge variables (3.68), with only 62.1% of the students confirming its importance. Emergency planning skills recorded the lowest mean among the financial skills variables (3.42), with only 58.2% of the students confirming their ability to do so. Most alarmingly, the saving culture recorded a mean of 3.42, which is lower than all three financial literacy variables. Only 53.0% of the students save a portion of their income on a monthly basis, and only 50.3% have emergency funds, despite 81.7% confirming the importance of emergency funds. Furthermore, only 54.3% of the students save before entertainment and leisure. The conclusion of the study is that despite the high level of financial literacy among MUBS students, there is a lack of saving due to social pressures and irregular income.
Undergraduate